2004
DOI: 10.1007/bf03325040
|View full text |Cite
|
Sign up to set email alerts
|

Eating attitudes across age and gender groups: A Canadian study

Abstract: Although EAT-26 is widely used in clinical and non-clinical population, age and gender comparisons have not been made in a population-based sample. Use of the subscales of eating attitudes should help health professionals better identify those at risk for eating disturbances and provide the opportunity for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
13
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 43 publications
6
13
0
1
Order By: Relevance
“…Indeed another study conducted in urban South Africa found lower rates of disordered eating attitude of 3.5% with the authors concluding that "ethnicity per se may not 'protect' against the development of disordered eating attitudes and behaviors in non-Western Black populations" 24 . Our study can also be compared with similar studies conducted in Iran, Brazil and Canada where prevalence rates of 24.2%, 13.4%, and 8.4% respectively have been reported 3,31,44 . The Canadian sample however comprised of people between 18 and 98 years of age.…”
Section: Discussionsupporting
confidence: 55%
“…Indeed another study conducted in urban South Africa found lower rates of disordered eating attitude of 3.5% with the authors concluding that "ethnicity per se may not 'protect' against the development of disordered eating attitudes and behaviors in non-Western Black populations" 24 . Our study can also be compared with similar studies conducted in Iran, Brazil and Canada where prevalence rates of 24.2%, 13.4%, and 8.4% respectively have been reported 3,31,44 . The Canadian sample however comprised of people between 18 and 98 years of age.…”
Section: Discussionsupporting
confidence: 55%
“…In this regard, gender differences in responsibilities for meal preparation and food shopping (16), food preferences and intakes (17), nutrition knowledge (18), interest in learning about health and nutrition (19), and eating behaviors (20)(21)(22)(23) have been highlighted in the literature. These differences may influence the quality of diet and the degree of adherence to healthy dietary recommendations (24).…”
Section: Introductionmentioning
confidence: 99%
“…Johnson and Bedford's study also showed that the combined dependent variables (Food Preoccupation, Image Preoccupation and External Focus) were significantly affected by gender but not age 12 . Through the three surveys with different participants groups, we may draw a conclusion that in comparison to BMI and gender, age has a limited effect on the psychological and behavioral traits relevant to eating disorders.…”
Section: Discussionmentioning
confidence: 89%
“…Mclean, Paxton and Wertheim found that in the EDE-Q subscales: the Body Dissatisfaction and disordered eating symptoms were unrelated to age 13 . Johnson and Bedford's study in Canada across gender and age groups, demonstrated that age was partly significantly correlated with the scores on the questionnaire EAT 12 . In Johnson and Bedford's study, the young participants (18-34 years) (both genders) showed significantly high levels of Food Preoccupation and Image Preoccupation on questionnaire EAT, in comparison with those in the 35-64 years group and the over 65 years group, but there was no difference in the External Focus subscale across all age groups 12 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation